Implementation of Digital Literacy to Develop Social Emotional in Early Childhood - Latifatus Saleha; Hasan Baharun; Winda Trimelia Utami (Indonesian Journal of Early Childhood Educational Research (IJECER), 2022)
This study aims to analyze the implementation of digital literacy in early childhood for childrenÔÇÖs social and emotional development. Qualitative research was used and a case study was chosen as the research design. Data were collected by observing and recording learning activities in schools. Interviews were conducted with principals and teachers at kindergarten. Results of the study showed that digital literacy was carried out through learning analysis, learning design system, and evaluation. This study implies that teachers must have innovation and creativity in managing their learning, especially in the era of society 5.0. Digitalization could support the instructional needs based on the intended targets and generate studentsÔÇÖ motivation and intelligence overall.┬á┬á